Non-aqueous electrolyte secondary battery

A dual-layer positive electrode structure in nonaqueous electrolyte secondary batteries, utilizing Ni and Ca in the first layer and Ni and Sr in the second layer, effectively addresses the challenge of increasing capacity while maintaining improved cycle characteristics, resulting in enhanced battery performance.

JP7665440B2Active Publication Date: 2025-04-21PANASONIC ENERGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021103974
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-23
Publication Date
2025-04-21
Estimated Expiration
2041-06-23

AI Technical Summary

Technical Problem

Existing nonaqueous electrolyte secondary batteries face challenges in increasing capacity while maintaining improved cycle characteristics, particularly when using lithium transition metal composite oxides with high Ni content, which can lead to side reactions and deterioration of battery performance.

Method used

The battery design incorporates a positive electrode with a dual-layer structure, where the first layer contains Ni and Ca, and the second layer contains Ni and Sr, with a lower Ni content in the second layer. This configuration enhances capacity and cycle stability by minimizing side reactions and transition metal element elution.

Benefits of technology

This approach results in a nonaqueous electrolyte secondary battery with high capacity and improved cycle characteristics, as evidenced by higher capacity retention rates compared to previous technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665440000003
    Figure 0007665440000003
  • Figure 0007665440000004
    Figure 0007665440000004
  • Figure 0007665440000001
    Figure 0007665440000001
Patent Text Reader

Abstract

To provide a non-aqueous electrolyte secondary battery with high capacitance and with improved cycle characteristics.SOLUTION: A non-aqueous electrolyte secondary battery comprises: a positive electrode; a negative electrode; a separator isolating the positive and negative electrodes from each other; and a non-aqueous electrolyte. The positive electrode has a positive electrode current collector, and a positive electrode mixture layer formed on a surface of the positive electrode current collector. The positive electrode mixture layer includes: a first positive electrode mixture layer opposed to the positive electrode current collector; and a second positive electrode mixture layer laminated on a surface of the first positive electrode mixture layer. The first positive electrode mixture layer includes a first positive electrode active material containing Ni and Ca. The second positive electrode mixture layer includes a second positive electrode active material containing Ni and Sr. The percentage content of Ni in the second positive electrode active material is lower than that in the first positive electrode active material.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]

[0002] In non-aqueous electrolyte secondary batteries, electrodes are generally used in which a mixture layer is formed on the surface of a current collector made of metal foil. The mixture layer contains an active material that can reversibly insert and remove Li, and the characteristics of the battery can be changed by changing the type of active material contained in the mixture layer or the distribution of the active material in the mixture layer.

[0003] Patent Document 1 discloses a positive electrode having a mixture layer made up of multiple layers, and describes that the cycle characteristics of a battery are improved by making the Co content in the layer farther from the current collector higher than the Co content in the layer closer to the current collector. Patent Document 2 discloses a positive electrode having a mixture layer made up of multiple layers, and describes that the cycle characteristics are improved while a high capacity is obtained by making the Mn content in the layer closer to the current collector equal to or higher than a predetermined value and making the Mn content in the layer farther from the current collector lower than the Mn content in the layer closer to the current collector. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 10-255762 [Patent Document 2] JP 2015-115244 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, in order to increase capacity, lithium transition metal composite oxides such as lithium nickel cobalt oxide are sometimes used as positive electrode active materials. By increasing the Ni content in the lithium transition metal composite oxide, it is possible to further increase capacity, but the cycle characteristics are likely to decrease due to side reactions between the positive electrode active material and the non-aqueous electrolyte. The techniques of Patent Documents 1 and 2 do not take into consideration a technique for suppressing the decrease in cycle characteristics due to side reactions while increasing the Ni content in the positive electrode active material to increase capacity, and there is still room for improvement.

[0006] An object of the present disclosure is to provide a nonaqueous electrolyte secondary battery with high capacity and improved cycle characteristics. [Means for solving the problem]

[0007] A non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode, a negative electrode, a separator that isolates the positive electrode and the negative electrode from each other, and a non-aqueous electrolyte. The positive electrode has a positive electrode current collector and a positive electrode mixture layer formed on a surface of the positive electrode current collector. The positive electrode mixture layer includes a first positive electrode mixture layer facing the positive electrode current collector and a second positive electrode mixture layer laminated on the surface of the first positive electrode mixture layer. The first positive electrode mixture layer includes a first positive electrode active material containing Ni and Ca. The second positive electrode mixture layer includes a second positive electrode active material containing Ni and Sr. The Ni content of the second positive electrode active material is lower than the Ni content of the first positive electrode active material. Effect of the Invention

[0008] According to one aspect of the present disclosure, a nonaqueous electrolyte secondary battery having high capacity and improved cycle characteristics can be provided. [Brief description of the drawings]

[0009] [Figure 1] 1 is an axial cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment of the present invention; [Diagram 2] FIG. 2 is a cross-sectional view of a positive electrode in one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] An example of an embodiment of a nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail below. A cylindrical battery in which a wound electrode body is housed in a cylindrical exterior body will be exemplified below, but the electrode body is not limited to the wound type, and may be a laminated type in which multiple positive electrodes and multiple negative electrodes are alternately laminated one by one with a separator interposed therebetween. In addition, the exterior body is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, or the like. It may be a pouch type composed of a laminate sheet including a metal layer and a resin layer.

[0011] Fig. 1 is an axial cross-sectional view of a cylindrical secondary battery 10 as one example of an embodiment. In the secondary battery 10 shown in Fig. 1, an electrode body 14 and a non-aqueous electrolyte (not shown) are housed in an exterior body 15. The electrode body 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. In the following description, for convenience of explanation, the sealing body 16 side will be referred to as the "upper" and the bottom side of the exterior body 15 as the "lower".

[0012] The upper end of the exterior body 15 is sealed with the sealing body 16, so that the inside of the secondary battery 10 is sealed. Insulating plates 17 and 18 are provided above and below the electrode body 14, respectively. The positive electrode lead 19 extends upward through the through hole of the insulating plate 17 and is welded to the lower surface of the filter 22, which is the bottom plate of the sealing body 16. In the secondary battery 10, the cap 26, which is the top plate of the sealing body 16 electrically connected to the filter 22, serves as the positive electrode terminal. On the other hand, the negative electrode lead 20 extends to the bottom side of the exterior body 15 through the through hole of the insulating plate 18 and is welded to the inner bottom surface of the exterior body 15. In the secondary battery 10, the exterior body 15 serves as the negative electrode terminal. Note that, when the negative electrode lead 20 is provided at the outer end of the winding, the negative electrode lead 20 passes outside the insulating plate 18, extends to the bottom side of the exterior body 15, and is welded to the inner bottom surface of the exterior body 15.

[0013] The exterior body 15 is, for example, a cylindrical metal exterior can with a bottom. A gasket 27 is provided between the exterior body 15 and the sealing body 16 to ensure the sealing of the interior of the secondary battery 10. The exterior body 15 has a grooved portion 21 that supports the sealing body 16 and is formed, for example, by pressing a side portion from the outside. The grooved portion 21 is preferably formed in an annular shape along the circumferential direction of the exterior body 15, and supports the sealing body 16 on its upper surface via the gasket 27.

[0014] The sealing body 16 includes a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25, and a cap 26, which are stacked in this order from the electrode body 14 side. Each member constituting the sealing body 16 has, for example, a disk shape or a ring shape, and each member except the insulating member 24 is electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective centers, and the insulating member 24 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, for example, the lower valve body 23 breaks, and the upper valve body 25 swells toward the cap 26 and separates from the lower valve body 23, thereby cutting off the electrical connection between them. When the internal pressure further increases, the upper valve body 25 breaks, and gas is discharged from the opening 26a of the cap 26.

[0015] The positive electrode 11, the negative electrode 12, the separator 13, and the non-aqueous electrolyte that constitute the electrode assembly 14 will be described in detail below, with the positive electrode 11 being particularly described.

[0016] [Positive electrode] The positive electrode 11 has a positive electrode current collector 30 and a positive electrode mixture layer formed on the surface of the positive electrode current collector 30. For the positive electrode current collector 30, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, or a film having such a metal disposed on the surface layer, can be used. The thickness of the positive electrode current collector 30 is, for example, 10 μm to 30 μm. In this specification, "to" means a range including the upper limit and lower limit before and after "to".

[0017] The positive electrode mixture layer includes a first positive electrode mixture layer 32 facing the positive electrode current collector 30, and a second positive electrode mixture layer 34 laminated on the surface of the first positive electrode mixture layer 32. As shown in Fig. 2, the positive electrode mixture layer is preferably formed on both sides of the positive electrode current collector 30. The total thickness of the first positive electrode mixture layer 32 and the second positive electrode mixture layer 34 is, for example, 10 µm to 150 µm, and preferably 50 µm to 100 µm, on one side of the positive electrode current collector 30. The ratio of the thickness of the first positive electrode mixture layer 32 to the thickness of the second positive electrode mixture layer 34 is, for example, 1:9 to 9:1.

[0018] The first positive electrode mixture layer 32 includes a first positive electrode active material containing Ni and Ca, and the second positive electrode mixture layer 34 includes a second positive electrode active material containing Ni and Sr. The Ni content of the second positive electrode active material is lower than the Ni content of the first positive electrode active material. This makes it possible to achieve battery performance with high capacity and excellent cycle characteristics.

[0019] The first positive electrode active material and the second positive electrode active material are, for example, lithium transition metal composite oxides. The lithium transition metal composite oxides have a layered rock salt structure including a transition metal layer, a Li layer, and an oxygen layer, and the Li ions present in the Li layer reversibly enter and exit the Li layer, thereby causing the charge and discharge reaction of the battery to proceed. By making the lithium transition metal composite oxide contain a metal element other than the transition metal, such as Ca or Sr, it is possible to suppress side reactions between the lithium transition metal composite oxide and the electrolyte. However, even if a lithium transition metal composite oxide containing Ca, Sr, etc. is used, the cycle characteristics may be significantly reduced.

[0020] The inventors of the present application have conducted intensive research into the above-mentioned problem, and as a result, it has been found that when cycle characteristics are degraded, the electrolyte salt concentration varies more in the portion close to the surface of the positive electrode mixture layer than in the portion close to the positive electrode current collector 30 of the positive electrode mixture layer, and the negative electrode active material deteriorates due to the elution of transition metal elements from the first positive electrode active material and the second positive electrode active material, resulting in a decrease in the capacity of the negative electrode. That is, the inventors of the present application have found that the above-mentioned phenomenon can be suppressed by the positive electrode 11 including the above-mentioned first positive electrode mixture layer 32 and second positive electrode mixture layer 34. In the portion close to the surface of the positive electrode mixture layer, the effect of Sr suppresses an increase in reaction resistance due to a side reaction even if the electrolyte salt concentration varies. In the portion close to the positive electrode current collector 30, the Ni content is increased to achieve high capacity, while the effect of Ca suppresses the elution of transition metal elements from the first positive electrode active material, thereby preventing excessive deterioration of the negative electrode 12.

[0021] The content of Ni in the first positive electrode active material may be more than 90 mass% and 95 mass% or less with respect to the total mass of the metal elements excluding Li, and the content of Ni in the second positive electrode active material may be 80 mass% or more and 90 mass% or less with respect to the total mass of the metal elements excluding Li. This allows the capacity of the battery to be further increased. The contents of elements such as Ni, Ca, and Sr constituting the first positive electrode active material and the second positive electrode active material can be measured, for example, by an inductively coupled plasma atomic emission spectrometer (ICP-AES).

[0022] The Ca content in the first positive electrode active material may be 0.03% by mass or more and 0.5% by mass or less, based on the total mass of the metal elements excluding Li, and the Sr content in the second positive electrode active material may be 0.03% by mass or more and 0.5% by mass or less, based on the total mass of the metal elements excluding Li, thereby making it possible to more significantly suppress the deterioration of cycle characteristics.

[0023] The first positive electrode active material may contain elements such as Co and Al in addition to Ni and Ca. The content of Co in the first positive electrode active material is preferably 0% by mass to 15% by mass, and more preferably 1% by mass to 10% by mass, based on the total mass of metal elements excluding Li. The content of Al in the first positive electrode active material is preferably 0% by mass to 10% by mass, and more preferably 0% by mass to 5% by mass, based on the total mass of metal elements excluding Li.

[0024] The second positive electrode active material may contain elements such as Co and Al in addition to Ni and Sr. The content of Co in the second positive electrode active material is preferably 0% by mass to 20% by mass, and more preferably 5% by mass to 15% by mass, based on the total mass of metal elements excluding Li. The content of Al in the second positive electrode active material is preferably 0% by mass to 10% by mass, and more preferably 0% by mass to 5% by mass, based on the total mass of metal elements excluding Li.

[0025] The first positive electrode active material and the second positive electrode active material are, for example, secondary particles formed by agglomeration of a plurality of primary particles. The particle size of the primary particles constituting the secondary particles is, for example, 0.05 μm to 1 μm. The particle size of the primary particles is measured as the diameter of a circumscribed circle in a particle image observed by a scanning electron microscope (SEM).

[0026] The volume-based median diameter (D50) of the secondary particles of the first positive electrode active material and the second positive electrode active material is, for example, 1 μm to 30 μm, preferably 3 μm to 20 μm. D50 means a particle size at which the cumulative frequency is 50% from the smallest particle size in the volume-based particle size distribution, and is also called the median diameter. The particle size distribution of the composite oxide (Z) can be measured using a laser diffraction type particle size distribution measuring device (for example, MT3000II manufactured by Microtrack Bell Co., Ltd.) with water as a dispersion medium.

[0027] In the first positive electrode active material, Ca is preferably present on the surface of the secondary particles or at the interface between the primary particles constituting the secondary particles. This makes it possible to more significantly suppress the elution of the transition metal element. Ca may form a Ca compound on the surface of the secondary particles or at the interface between the primary particles. Examples of Ca compounds include CaO, Ca(OH)2, and CaCO3.

[0028] In the second positive electrode active material, Sr is preferably present on the surface of the secondary particles or between the primary particles constituting the secondary particles. This makes it possible to more significantly suppress side reactions with the electrolyte. Sr may form an Sr compound on the surface of the secondary particles or at the interface between the primary particles. Examples of Sr compounds include SrO, Sr(OH)2, and SrCO3.

[0029] The first positive electrode mixture layer 32 and the second positive electrode mixture layer 34 may contain a conductive agent, a binder, and the like in addition to the first positive electrode active material or the second positive electrode active material.

[0030] Examples of the conductive agent contained in the first positive electrode mixture layer 32 or the second positive electrode mixture layer 34 include carbon-based particles such as carbon black (CB), acetylene black (AB), ketjen black, carbon nanotubes (CNT), graphene, graphite, etc. These may be used alone or in combination of two or more kinds.

[0031] Examples of the binder contained in the first positive electrode mixture layer 32 or the second positive electrode mixture layer 34 include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide-based resins, acrylic-based resins, polyolefin-based resins, etc. These may be used alone or in combination of two or more.

[0032] The first positive electrode mixture layer 32 and the second positive electrode mixture layer 34 are manufactured using, for example, a first positive electrode mixture slurry containing a first positive electrode active material, a conductive agent, and a binder, and a second positive electrode mixture slurry containing a second positive electrode active material, a conductive agent, and a binder. Specifically, the first positive electrode mixture slurry is applied to both sides of the positive electrode current collector 30, the coating is dried to form the first positive electrode mixture layer 32, and then the second positive electrode mixture slurry is applied to substantially the entire surface of the first positive electrode mixture layer 32, and the coating is dried to form the second positive electrode mixture layer 34. Thereafter, the first positive electrode mixture layer 32 and the second positive electrode mixture layer 34 are rolled using a roller or the like to produce the positive electrode 11. In the above method, the first positive electrode mixture slurry is applied and dried, and then the second positive electrode mixture slurry is applied, but the second positive electrode mixture slurry may be applied after the first positive electrode mixture slurry is applied and before drying. Also, the second positive electrode mixture slurry may be applied after the first positive electrode mixture slurry is applied, dried, and rolled.

[0033] [Negative electrode] The negative electrode 12 has a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. The negative electrode current collector can be a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film with the metal disposed on the surface. The thickness of the negative electrode current collector is, for example, 5 μm to 30 μm.

[0034] The negative electrode mixture layer is preferably formed on both sides of the negative electrode current collector. The thickness of the negative electrode mixture layer is, for example, 10 μm to 150 μm on one side of the negative electrode current collector. The negative electrode mixture layer contains, for example, a negative electrode active material and a binder. The negative electrode can be produced, for example, by applying a negative electrode mixture slurry containing a negative electrode active material, a binder, and the like to both sides of the negative electrode current collector, drying the coating, and then rolling the negative electrode mixture layer using a roller or the like.

[0035] The negative electrode active material is not particularly limited as long as it can reversibly occlude and release lithium ions, and generally carbon materials such as graphite are used. The graphite may be any of natural graphite such as flake graphite, massive graphite, and earthy graphite, massive artificial graphite, and artificial graphite such as graphitized mesophase carbon microbeads. Further, as the negative electrode active material, metals that alloy with Li such as Si and Sn, metal compounds containing Si, Sn, etc., lithium titanium composite oxides, etc. may be used. For example, SiO x (0.5 ≦ x ≦ 1.6), or Li 2y SiO (2+y) Si-containing compounds in which fine particles of Si are dispersed in a lithium silicate phase represented by (0 < y < 2), etc. may be used in combination with graphite.

[0036] As the binder contained in the negative electrode binder layer, similar to the case of the positive electrode, fluorine-containing resins such as PTFE and PVDF, PAN, polyimide, acrylic resin, polyolefin, etc. may be used, but preferably styrene-butadiene rubber (SBR) is used. Further, the negative electrode binder layer may contain CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. The negative electrode binder layer contains, for example, SBR and CMC or its salt.

[0037] [Separator] The separator 13 has a function of isolating the positive electrode 11 and the negative electrode 12 from each other. A porous sheet having ion permeability and insulation is used for the separator 13. Specific examples of the porous sheet include microporous thin films, woven fabrics, non-woven fabrics, etc. As the material of the separator, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 may have a single-layer structure or may have a laminated structure. Further, a resin layer with high heat resistance such as an aramid resin, a filler layer containing an inorganic compound filler may be provided on the surface of the separator 13.

[0038] [Non-aqueous electrolyte] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more of these can be used as the non-aqueous solvent. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen atoms of these solvents is substituted with a halogen atom such as fluorine. Examples of the halogen-substituted product include fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, and fluorinated chain carboxylates such as methyl fluoropropionate (FMP).

[0039] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.

[0040] Examples of the above ethers include cyclic ethers such as 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, crown ether, etc., and chain ethers such as 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.

[0041] The electrolyte salt is preferably a lithium salt. Examples of the lithium salt include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), etc., LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1SO2){l, m are integers of 0 or more} and other imide salts. The lithium salt may be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoints of ion conductivity, electrochemical stability, and the like. The concentration of the lithium salt is preferably 0.8 mol to 1.8 mol per 1 L of the non-aqueous solvent, for example. EXAMPLES

[0042] The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.

[0043] <Example 1> [Preparation of positive electrode active material] The first positive electrode active material used was lithium transition metal composite oxide particles containing metal elements other than Li in the mass ratio shown in Table 1. In the lithium transition metal composite oxide, the molar ratio of Li to the metal elements other than Li was 1:1. The lithium transition metal composite oxide was obtained by mixing a composite oxide containing Ni, Co, and Al in the mass ratio shown in Table 1, CaO, and LiOH as a Li source, and baking the mixture.

[0044] The second positive electrode active material used was lithium transition metal composite oxide particles containing metal elements other than Li in the mass ratio shown in Table 1. In the lithium transition metal composite oxide, the molar ratio of Li to the metal elements other than Li was 1:1. The lithium transition metal composite oxide was obtained by mixing a composite oxide containing Ni, Co, and Al in the mass ratio shown in Table 1, SrO, and LiOH as a Li source, and baking the mixture.

[0045] [Preparation of positive electrode] A mixture was prepared by mixing 95 parts by mass of the first positive electrode active material and 5 parts by mass of graphite as a conductive agent. This mixture was mixed with polyvinylidene fluoride (PVDF) in a mass ratio of 95:5, and kneaded while adding N-methyl-2-pyrrolidone (NMP) to prepare a first positive electrode mixture slurry. Next, the first positive electrode mixture slurry was applied to both sides of a positive electrode current collector made of aluminum foil with a thickness of 16 μm by a doctor blade method, and the coating was dried to form a first positive electrode mixture layer (uncompressed state).

[0046] A mixture was prepared by mixing 95 parts by mass of the second positive electrode active material and 5 parts by mass of graphite as a conductive agent. This mixture was mixed with polyvinylidene fluoride (PVDF) in a mass ratio of 95:5, and kneaded while adding N-methyl-2-pyrrolidone (NMP) to prepare a second positive electrode mixture slurry. Next, the second positive electrode mixture slurry was applied to the surface of the first positive electrode mixture layer by a doctor blade method, and the coating was dried to laminate a second positive electrode mixture layer over the entire surface of the first positive electrode mixture layer. The first positive electrode mixture layer and the second positive electrode mixture layer were rolled using a roller to obtain a mixture layer density of 3.6 g / cm. 3 After that, the sheet was cut to a predetermined electrode size to prepare a strip-shaped positive electrode. After rolling, the thickness of the first positive electrode mixture layer and the thickness of the second positive electrode mixture layer were approximately the same. In addition, an exposed portion was provided in a part of the positive electrode where the positive electrode current collector was exposed, and one end of an Al positive electrode lead was fixed to the exposed portion by ultrasonic welding.

[0047] [Preparation of negative electrode] Artificial graphite, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 96:2:2, and an appropriate amount of water was added to prepare a negative electrode mixture slurry. Next, the negative electrode mixture slurry was applied to both sides of a negative electrode current collector made of copper foil with a thickness of 12 μm by a doctor blade method, and the coating was dried. The dried coating was rolled using a roller to obtain a mixture layer density of 1.55 g / cm. 3 After that, the negative electrode was cut to a predetermined electrode size to prepare a strip-shaped negative electrode. In addition, an exposed portion was provided in a part of the negative electrode where the negative electrode current collector was exposed, and one end of a Ni negative electrode lead was fixed to the exposed portion by ultrasonic welding.

[0048] [Preparation of electrolyte] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 20:20:60 (25°C, 1 atm). LiPF6 was dissolved in the mixed solvent at a concentration of 1.2 mol / L to prepare an electrolyte solution.

[0049] [Preparation of secondary battery] The positive and negative electrodes were wound in a spiral shape with a separator of a microporous film made of an olefin resin interposed therebetween to prepare a wound electrode body. Insulating plates were placed on the top and bottom of the electrode body, respectively, and the electrode body was housed in an outer can. The outer can had an external shape of 65 mm in height and 18 mm in diameter. The negative electrode lead was welded to the bottom of the cylindrical outer can with a bottom, and the positive electrode lead was welded to the sealing body. After injecting a nonaqueous electrolyte into the outer can, the opening of the outer can was sealed with the sealing body via a gasket to prepare a nonaqueous electrolyte secondary battery.

[0050] [Evaluation of capacity retention rate] The secondary battery was charged to 4.2 V at a constant current of 0.5 C at an ambient temperature of 25° C., and then charged to 1 / 50 C at a constant voltage of 4.2 V. Thereafter, the battery was discharged to 2.5 V at a constant current of 0.2 C, and the discharge capacity at this time was taken as the initial discharge capacity.

[0051] Next, the secondary battery was charged to 4.2 V at a constant current of 0.5 C at an ambient temperature of 25° C., charged to 1 / 50 C at a constant voltage of 4.2 V, and then discharged to 2.5 V at a constant current of 1.0 C. This charge / discharge cycle was counted as one cycle, and 500 cycles were performed.

[0052] The secondary battery for the cycle test was charged to 4.2 V at a constant current of 0.5 C at an environmental temperature of 25° C., and then charged to 1 / 50 C at a constant voltage of 4.2 V. It was then discharged to 2.5 V at a constant current of 0.2 C, and the discharge capacity at this time was taken as the discharge capacity after 500 cycles. The capacity retention rate was calculated from the initial discharge capacity and the discharge capacity after 500 cycles using the following formula. Capacity retention rate (%) = (discharge capacity after 500 cycles ÷ initial discharge capacity) × 100

[0053] <Examples 2 to 18 and Comparative Examples 1 to 22> A secondary battery was produced and evaluated in the same manner as in Example 1, except that lithium transition metal composite oxide particles containing metal elements other than Li in the mass ratios shown in Tables 1 and 2 were used as the first and second positive electrode active materials. ZrO2, Y2O3, Nb2O5, and Mg were used as raw materials for Zr, Y, Nb, and Mg, respectively, when producing the lithium transition metal composite oxide particles.

[0054] The capacity retention rates of the examples are shown in Table 1, and the capacity retention rates of the comparative examples are shown in Table 2. In Table 1, α and β respectively represent metal elements other than Ni, Co, and Al in the first and second positive electrode active materials.

[0055] [Table 1]

[0056] [Table 2]

[0057] In all of the Examples, the capacity retention rate was higher than that of the Comparative Examples. That is, in the Examples, secondary batteries with high capacity and improved cycle characteristics were obtained. In particular, in Examples 1 to 10, the capacity retention rate was higher than that of Examples 11 to 18, and it was found that there are more preferable ranges for the Ni and Ca contents in the first positive electrode mixture layer and the Ni and Sr contents in the second positive electrode mixture layer. [Explanation of symbols]

[0058] REFERENCE SIGNS LIST 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 exterior body, 16 sealing body, 17, 18 insulating plate, 19 positive electrode lead, 20 negative electrode lead, 21 grooved portion, 22 filter, 23 lower valve body, 24 insulating member, 25 upper valve body, 26 cap, 26a opening, 27 gasket, 30 positive electrode current collector, 32 first positive electrode mixture layer, 34 second positive electrode mixture layer

Claims

1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a separator separating the positive electrode and the negative electrode from each other, and a non-aqueous electrolyte, The positive electrode has a positive electrode current collector and a positive electrode mixture layer formed on a surface of the positive electrode current collector, the positive electrode mixture layer includes a first positive electrode mixture layer facing the positive electrode current collector and a second positive electrode mixture layer laminated on a surface of the first positive electrode mixture layer, The first positive electrode mixture layer includes a first positive electrode active material containing Ni and Ca, The second positive electrode mixture layer includes a second positive electrode active material containing Ni and Sr, a Ni content in the second positive electrode active material is lower than a Ni content in the first positive electrode active material.

2. The content of Ni in the first positive electrode active material is more than 90 mass% and 95 mass% or less with respect to the total mass of metal elements excluding Li, 2 . The nonaqueous electrolyte secondary battery according to claim 1 , wherein the second positive electrode active material has a Ni content of 80% by mass or more and 90% by mass or less with respect to the total mass of metal elements excluding Li.

3. The content of Ca in the first positive electrode active material is 0.03 mass% or more and 0.5 mass% or less with respect to the total mass of metal elements excluding Li, 3 . The nonaqueous electrolyte secondary battery according to claim 1 , wherein the content of Sr in the second positive electrode active material is 0.03 mass % or more and 0.5 mass % or less with respect to the total mass of metal elements excluding Li.

Citation Information

Patent Citations

  • Lithium battery

    JP1998255762A

  • Positive electrode for lithium secondary battery, lithium secondary battery, battery module, and automobile mounting battery module

    JP2015115244A

  • Positive electrode for lithium ion secondary battery and battery using the same

    JP2018147790A

  • Positive electrode for lithium secondary battery, method for producing same, and lithium secondary battery including same

    JP2022532884A

  • JPP7461964B